Effects of Intranasal Orexin-A (Hypocretin-1) Administration on Neuronal Activation, Neurochemistry, and Attention in Aged Rats - Calva, Coleman B.; Fayyaz, Habiba; Fadel, Jim R. (Frontiers in Aging Neuroscience, 2020)
Cognitive function represents a key determinative factor for independent functioning amongst the elderly, especially among those with age-related cognitive disorders. However; existing pharmacotherapeutic tactics for treating these disorders provide only modest benefits on cognition. The hypothalamic orexin (hypocretin) system is uniquely positioned, anatomically and functionally, to integrate physiological functions that support proper cognition. The ongoing paucity of orexin receptor agonists has mired the ability to study their potential as cognitive enhancers. Fortunately, intranasal administration of native orexin peptides circumvents this issue and others concerning peptide transport into the CNS. To investigate the ability of intranasal orexin-A administration to improve the anatomical, neurochemical, and behavioral substrates of age-related cognitive dysfunction, these studies utilized a rodent model of aging combined with acute intranasal administration of saline or orexin-A. Here, intranasal orexin-A increases c-Fos expression in several telencephalic brain regions that mediate important cognitive functions, increases prefrontal cortical acetylcholine efflux, and alters set-shifting mediated attentional function in rats. Ultimately, these studies provide a framework for the possible mechanisms and therapeutic potential of intranasal orexin-A in treating age-related cognitive dysfunction.